Cerebral ischemia and hemorheology - Hartmann, Alexander; Kuschinsky, Wolfgang (Springer Berlin Heidelberg, 1987)
This book describes current knowledge on the interrelationship between hemorheology and cerebral ischemia. The most relevant experimental and clinical findings regarding the influence of hemorheological factors on cerebral ischemic disorders are presented. Contributions by experts from both the fields of cerebral circulation and rheology are included in order to broaden perspectives and encourage exchange between the two groups. The book will thus help establish new strategies for a better understanding of metabolic, circulatory and rheologic changes during cerebral ischemia